Efektivitas Penerapan Sanksi Administratif bagi Pelaku Usaha yang Tidak Memiliki Perizinan Berusaha Terintegrasi Secara Elektronik (OSS) - Chandra Sagala; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The Online Single Submission (OSS) system represents a licensing reform following the enactment of the Omnibus Law on Job Creation, which mandates business actors to possess a Business Identification Number (NIB). To enforce this obligation, the state implements administrative sanctions. This legal doctrinal study, employing statutory and conceptual approaches, aims to analyze the legal framework, the forms of sanction enforcement, and their effectiveness under Government Regulation Number 28 of 2025. The results indicate that administrative sanctions within the OSS regime are structured progressively, ranging from written warnings to license revocations. However, their effectiveness remains hindered by weak field oversight, overlapping institutional authority, low digital literacy among business actors, and underutilized government coercion (bestuursdwang). This study concludes that the effectiveness of administrative sanctions relies not merely on regulatory completeness, but on consistent implementation, institutional coordination, and strengthening the legal culture of business actors.